2022
DOI: 10.33975/riuq.vol34n1.558
|View full text |Cite
|
Sign up to set email alerts
|

Empoderamiento Social Y Organizacional Como Un Modelo De Investigación Para Alcanzar La Sustentabilidad

Abstract: El presente artículo es producto de una revisión de la literatura reciente sobre el empoderamiento organizacional y social como instrumentos para que los individuos en el ámbito organizacional y social participen e incidan en las decisiones que los afectan y se conviertan en actores del desarrollo. Ha sido construido con el objetivo de realizar una aproximación conceptual que informe la evolución histórica de las categorías empoderamiento, empoderamiento social y empoderamiento organizacional, desde una perspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
0
0
1
Order By: Relevance
“…De acuerdo con los autores [11], [28] el empoderamiento organizacional es un enfoque que da poder a los empleados para tomar decisiones y resolver problemas. Mejora la motivación, innovación, productividad y adaptabilidad de la empresa.…”
Section: Resultados Y Discusión A) El Empoderamientounclassified
“…De acuerdo con los autores [11], [28] el empoderamiento organizacional es un enfoque que da poder a los empleados para tomar decisiones y resolver problemas. Mejora la motivación, innovación, productividad y adaptabilidad de la empresa.…”
Section: Resultados Y Discusión A) El Empoderamientounclassified
“…In the case of education, it is not surprising that this hypothesis was confirmed to some extent, as there were already elements indicating its importance. Theory supports this significance by asserting that, in the case of education, pedagogical exercises will empower individuals to become active and engaged citizens who contribute to the growth and wellbeing of their communities (Jiménez-Munive et al, 2022). Additionally, it is claimed that, as education has the responsibility of forming conscious citizens, it needs to undergo a comprehensive transformation to maintain the validity of its role (Mejia González et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, greater regulation by the state to prevent capital accumulation in a single economic entity, thus promoting a balance in the participation of different economic entities to influence sustainable consumption, should prevail. Likewise, the importance of the government's role as a promoter of social organisations, companies, and citizens towards more democratic and participatory behaviour, facilitating the common good, prosperity, and social justice, has been discussed (Jiménez-Munive et al, 2022). Similarly, it has been concluded that the state, through social policies that protect citizens from market aggressions and seek to satisfy their most basic needs, will promote the transition to sustainability (Houtart, 2014).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation